REFLEKSI PENCIPTAAN TEATRIKAL TARI GOOD ANRONG - Sholihin, Muhammad Ibnu; Bantolo, Matheus Wasi (Institut Seni Indonesia Surakarta, 2023)
The research entitled Reflections on the Theatrical Creation of Good Anrong Dance is a research that focuses on tracing the process of creating Good Anrong Dance Theatrical works. This study reveals three problems, namely the reflection of mother's acceptance, the transformation of ideas into the creation process, and the form of presentation of the work. This study uses the Practice Based Research method. To dissect each problem, this study uses Kubler Ross theory to reveal the reflection of maternal acceptance, Wahyu Santoso prabowo's theory of net concepts, krenteg, karep, Lois Ellfeldt, Suzanne K Walther to analyze the transformation of ideas into the creation process, and the theory of Janet Adshead and Slamet MD to describe the form of presentation of the work. The data were collected through observation, literature study, and interviews. The results of the study show: first, the idea of the Theatrical work of Good Anrong Dance on the theme of Acceptance emerged as a form of criticism of social phenomena that underlies the formation of the idea of creating a reflection of mother's acceptance. Second, efforts to develop and express the idea of reflection of mother's acceptance into the form of work, continue with creative activities in the form of the stages of idea transformation carried out during the creation process. The stages of transforming ideas into the creation process include exploration, improvisation, evaluation, formation, training process, and presentation process. The theatrical work of Good Anrong Dance is a form of creativity and expression of freedom to the readers of the theme, taking into account the context of the form of creation. Theatrical work of Good Anrong Dance builds dramatic elements through dancers, movements, visual arrangements, and elements of sound, expression or feeling related to the theme and idea of the work.